PEMBUATAN ALAT TAMBAL BAN DALAM ELETRICK DENGAN TEKNOLOGI TIMER OTOMATIS - Setiawan, Feri; budiyono, budiyono; Prasetyo, imam (Universitas Muhammadiyah Pekajangan Pekalongan, 2018)
ABSTRACT ‘’MAKING THE ELECTRICAL EQUIPMENT TIRE AUTOMATIC TIMER WITH AUTO TECHNOLOGY’’ This final project aims to increase efficiency in filling the tires in the motorcycle and automobile, the function of making this tool in order to provide a level of convenience and security of the person at the time of application of the patch in the tire. For that it is necessary to modify the tire in a manual tool into the tool patched in elektrick and applies automatic timer technology. The modification process , changing tool patched in the manual is a tool tire elektrick technology with automatic timer begins with creating a framework tire, manufacture cradle for the self-timer and on / off, provision of pamanas electrical, supplying rubber to patch / compound, water reservoir, miserly smooth, providing the glue, and the application of the patch. Performance testing tool elektrick tire technology with automatic timers whole can be done by filling a test tube on a motorcycle or a car, the variables are seen is the result of different patches varying perfectly on time. Keywords: Tools tire, electrick and automatic timer.